Scrotal Circumference as Selection Criterion for Replacement Rams - Pabón-Quevedo, Héctor Yezid; Pulido-Medellín, Martín Orlando (Universidad Pedagógica y Tecnológica de Colombia, 2021)
To select the rams to become part of the herd, in the group of breeders, the evaluation of reproductive fitness has proven to be an excellent tool; this evaluation consists of a general physical examination, an andrological test and a spermogram. Within the andrological test, the measurement of scrotal circumference has been important, because it refers to the testicular size defined in centimeters, which is related to the ability of the testicle to produce sperm and therefore to the fertility of the reproductive male. Its use has spread because it is easy and reliable to measure; it presents significant correlations with morphometric measures, especially with body weight and is a heritable characteristic for future generations; This positive correlation has also been determined with the spermogram, since both semen volume, concentration and sperm quality have a direct relationship with the measurement of scrotal circumference. Finally, when the ram has been valued and is found fit to serve, it is the same ram that demonstrates the result with its service capacity, expressed in riding ability and libido or sexual desire. The evaluation of reproductive aptitude constitutes parameters for an efficient selection, in which factors inherent to the animal must also be considered, such as nutritional factors, environmental aspects, race and endocrine factors, which in one way or another can affect the sexual behavior of the ram. The objective of the present work was to carry out a literature review that allows identifying the usefulness of the andrological test in the ram, emphasizing the measurement of scrotal circumference as an indicator of sperm quality and reproductive efficiency for the selection of sires.